Isolamento, identificação e análise quimioinformática de triterpenos da espécie de Maytenus erythroxylon - Figueiredo, Pedro Thiago Ramalho de (2019)
Maytenus, a genus which belongs to the Celastraceae family, presents around 300 species distributed in the pantropical regions of the world. This genus has great relevance for the treatment of gastrointestinal disorders. Maytenus erythroxylon var. Maytenus erythroxyla is endemic to the northeast region of Brazil, recent studies have shown that the ethanolic extract of this species present a potent antidiarrheal activity. The aims of this work are to perform the phytochemical study of M. erythroxylon and to evaluate the antimicrobial activity of extracts and isolated substances. The aerial parts of M. erythroxylon were collected in the city of Mamanguape-PB were dried and triturate to obtain the vegetal powder that were extracted with ethanol for obtaining the crude ethanolic extract, this was submitted to chromatographic methods for isolation and purification of secondary metabolites. For the identification of the chemical structures of the secondary metabolites were used spectroscopic methods of Infrared and Nuclear Magnetic Resonance of 1H, 13C and bidimensional. From the defatted hexane fraction, were isolated five pentacyclic triterpenes with friedelane skeleton (3β-friedelanol, 3,4-seco-friedelan-3-oic acid and 3- oxo-30-hydroxyfriedelan) and two with lupan skeleton (norlupan-3,20-dione and 30-hydroxy-20 (29) - lupen-3-one). All compounds reported by the first in this species and 29-norlupan-3,20-dione were first isolated in the genus. In the Quantitative structure–activity relationship (QSAR) study, to evaluate the prediction of the activities of the isolated substances against the microorganisms Salmonella enteritidis, Escherichia coli, Pseudomonas aeruginosa and Candida albicans. The compounds were classified according to pMIC50 values to generate and validate the model by "Random Forest" (RF). The RF prediction model for the mentioned microorganisms obtained a percentage of accuracy above 72%, area under the curve, Receiver Operating Characteristic (ROC), above 0.8. From this study, isolated triterpene 3,4-seco-friedelan-3-oic acid was considered active for the C. albicans model. At the same time, the study of molecular docking of the isolated substances with the enzymes 14α-lanosteroldemethylase, exo-beta- (1,3) -glucanase and N-Myristoyltransferase. From this study, the triterpenes 3,4-seco-friedelane, 30-hydroxy- (20) -29-lupen-3-one and 29-norlupan-3,20-dione showed better binding energies in the interaction with 14α-lanosterol -dimethylase and triterpenes-3,4-seco-friedelane, 3-oxo-30-hydroxyfriedelane and 3β-friedelanol showed better binding energies in the interaction with exo-beta- (1,3) -glucanase. All of the triterpenes cited had similar interactions with the binders described in the literature. The antimicrobial activity of the isolated phases and substances was studied using the bacterial strains S. enteritidis (ATCC-6017), S. enteritidis (LM-13), E. coli (ATCC-18739), P. aeruginosa and fungal strains C. albicans (ATCC-60193), C. tropicalis (ATCC-13803). This study revealed that the products tested inhibited yeast strains.